2019
DOI: 10.1002/ejlt.201900354
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity Evaluation of Tocored through Chemical Assays, Evaluation in Stripped Corn Oil, and CAA Assay

Abstract: γ‐Tocopherol‐5,6‐quinone (tocored) is a crucial oxidized product of γ‐tocopherol (γ‐T) found in edible oil. Previously published studies on antioxidant activity (AOA) of tocored are not consistent. This study aims to monitor its AOA comprehensively through chemical assays (1,1‐diphenyl‐2‐picrylhydrazyl [DPPH] and ferric reducing antioxidant power [FRAP]), antioxidant evaluation in a food model system (stripped corn oil), and cellular antioxidant activity (CAA) assay, which would reasonably widen the knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…The need for antioxidant agents that can reduce the free radical levels in various parts of the body is absolutely crucial and this effect can be seen in some oils. Corn Oil has been concluded to be a potent antioxidant agent from results of chemical assays 12 . Another study on the body weight, biochemical, and haematological parameters have also proved the capability of corn oil has on the liver and kidneys of rats, further highlighting its antioxidant prowess 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The need for antioxidant agents that can reduce the free radical levels in various parts of the body is absolutely crucial and this effect can be seen in some oils. Corn Oil has been concluded to be a potent antioxidant agent from results of chemical assays 12 . Another study on the body weight, biochemical, and haematological parameters have also proved the capability of corn oil has on the liver and kidneys of rats, further highlighting its antioxidant prowess 13 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings aligns with Zheng's previous research, which also reported a positive correlation between CAA and concentration of single addition. 22 Interestingly, when the two were combined at a fixed ratio of 1 : 10 and tested at different concentrations, the CAA values exhibited a biphasic tendency. Initially, there was an increase in CAA values, followed by a subsequent decrease.…”
Section: Antioxidant Interaction Of Minor Constituentsmentioning
confidence: 96%
“…In addition, at present, knowledge about the mechanism of color reversion is also limited due to the complex transformations of tocored in oil systems [ 35 ]. Tocored has been shown to have antioxidant activity [ 42 , 43 ], and it might be oxidized during the color reversion process [ 5 ]. Significantly, the effect of the oxidation products of tocored on color reversion should not be ignored, as the contribution of the oxidation products of tocored to color reversion is not yet fully understood.…”
Section: The Mechanism Of Color Reversionmentioning
confidence: 99%